The Impact of Payment Frequency on Consumer Spending and Subjective Wealth Perceptions - De La Rosa, Wendy; Tully, Stephanie M (Journal of Consumer Research, 2022)
Abstract Payment frequency is a fundamental yet underexplored feature of consumers’ finances. As higher payment frequencies are becoming more prevalent, consumers are receiving more frequent yet smaller paychecks. An analysis of income and expenditure data of over 30,000 consumers from a financial services provider demonstrates a naturally occurring relationship between higher payment frequencies and increased spending. A series of lab studies support this finding, providing causal evidence that higher (vs. lower) payment frequencies increase spending. The effect of payment frequency on spending is driven by changes in consumers’ subjective wealth perceptions. Specifically, higher payment frequencies reduce consumers’ uncertainty in predicting whether they will have enough resources throughout a period, increasing their subjective wealth perceptions. As such, situational factors that reduce prediction uncertainty for those paid less frequently (e.g., the timing of consumers’ expenses, income levels) moderate the impact of payment frequency. The effects of payment frequency on subjective wealth and spending can occur even when objective wealth favors those with lower payment frequencies. More broadly, the current work underscores a need to understand how timing variations in consumers’ income impact their perceptions, behaviors, and general well-being.